Percepção das práticas de higiene bucal em Unidade de Terapia Intensiva - OLIVEIRA, Karla Conceição Costa (2019)
Poor oral hygiene is common in intensive care unit (ICU) patients and is associated with accumulation of dental biofilm, bacterial colonization of the oropharynx, and increased rate of ventilator-associated pneumonia (VAP). Oral hygiene (HB) is the care provided to restore and maintain the microbiological balance of the oral cavity and is attributed by the nursing team to the inability of the patient to perform self-care. There is evidence that team knowledge about HB influences the care provided. This study aimed to identify and analyze the perceptions of the nursing team regarding the importance, knowledge and clinical practices of HB provided to ICU patients. The present research presented a quantitative and qualitative approach, targeting nursing professionals (nurses and nursing technicians) who work in the General Adult ICU of the University Hospital of the Federal University of Maranhão (HUUFMA) located in the city of São Luís-MA in the period of August and September of 2018. Participated in the study 57 professionals by means of sample selection for convenience. The research in question used two instruments of data collection: interview and questionnaire. In the view of the interviewees, HB is important and brings benefits to patients hospitalized in ICU, however there are innumerable difficulties encountered by the nursing team in the execution of care. The lack of specific training was mentioned by the professionals interviewed as well as the need for training and effective presence of the Dentist in the team. Most professionals (75%) claimed to have knowledge about toothbrushing techniques, but less than half (43.64%) have already received some training in HB. The use of dental brushes presented a significant difference (p = 0.03) among the professional categories, since 64.29% of the nurses advised the use of toothbrushes while 90,70% of the technicians used it in the execution of HB. The variability of chlorhexidine concentrations used in HB mentioned by the professionals of the ICU under study indicates the lack of conformity with the protocol established by said hospital. A little more than half of the participants (53.57%) presented the perception of differentiated attention in the management of patients in MV when compared with conscious patients. In this sense, we can conclude that the nursing team studied presents an excellent perception regarding the importance of HB to ICU patients, but poor standardization in the clinical routine with numerous difficulties in the daily execution of the care possibly related to lack of skills and absence of the Dentist in the multidisciplinary team of the ICU.